Relationship Change, Network Change, and the Use of Single Name Generators in Longitudinal Research on Social Support. Issue 1 (February 2021) - Marin, Alexandra; Dubash, Soli
As relationships change and people change the kinds of support they provide, name generators that collect information about ties that provide particular kinds of support at repeated points of time may not effectively capture ties that are active but whose roles have changed. This article shows that a significant minority of network members change the kinds of support they provide. They either discontinue a support previously provided or provide a new type of support. We examine the implications of this finding for longitudinal studies of support networks based on single name generators and show that this practice can result in frequent misperceptions of network membership change.